Method for improving iron grade of magnetic separation iron ore concentrate of copper separation tailings of copper smelting slag
By using dilute sulfuric acid leaching and magnetic separation processes, the problem of inefficient recovery of iron resources from copper smelting slag has been solved, resulting in high-grade iron concentrate, simplified processes, reduced costs, and promoted the development of green metallurgy.
Patent Information
- Application Number
- CN202511709566.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-01-30
AI Technical Summary
Existing technologies are insufficient for the efficient recovery of iron resources from copper smelting slag. Conventional processes are complex, costly, and inefficient, resulting in the ineffective utilization of copper tailings.
Copper tailings are selected by leaching copper smelting slag with dilute sulfuric acid solution, combined with grinding and magnetic separation processes. By selectively decomposing the ferrolithite phase, the intergrowth structure of magnetite and gangue minerals is broken, thereby improving the degree of liberation and recovery rate of magnetite.
It achieves efficient recovery of high-grade iron concentrate, with an iron recovery rate of over 75%. The process is simple, the cost is controllable, and it aligns with the development direction of green metallurgy.
Smart Images

Figure CN121428256A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of hydrometallurgy and comprehensive recovery of secondary resources, and particularly relates to a method for improving the iron grade of a magnetic separation iron concentrate from copper smelting slag tailing. BACKGROUND
[0002] Copper is an important industrial metal, and the global refined copper production has maintained a steady growth trend for a long time. Pyrometallurgical smelting is one of the current mainstream copper production processes. In the process of pyrometallurgical copper smelting, 2-3 tons of copper smelting slag are usually produced for every ton of copper. Long-term accumulation leads to a huge amount of copper smelting slag in stock. As a typical non-ferrous metal secondary resource, copper smelting slag is rich in iron, copper and other valuable components, and has a very high recycling value.
[0003] At present, most copper smelting enterprises only use the slow cooling-flotation process to separate and recover copper elements in copper smelting slag, and do not pay enough attention to the recovery of iron and other valuable components in the flotation by-product (i.e. copper tailing). In fact, the iron content in copper smelting slag tailing is usually about 40%, which is significantly higher than the conventional iron ore grade that can be mined, and has the potential to be developed as an iron resource. However, due to the mineral structure characteristics of copper smelting slag tailing, the magnetite is closely combined with silicate and amorphous substances, and the content of magnetite itself is relatively low. Therefore, the conventional iron ore recovery process cannot achieve efficient separation and enrichment of iron, resulting in a large amount of copper tailing that cannot be effectively utilized and can only be stockpiled for a long time.
[0004] From the perspective of resource utilization and environmental protection, if the efficient recovery of iron resources in copper smelting slag tailing can be achieved, not only can it create considerable economic benefits and alleviate the global iron ore supply and demand imbalance, but also it can promote the recycling of secondary resources and reduce the environmental pressure caused by the stockpiling of industrial solid waste, which is of great significance to support the development of green metallurgical industry.
[0005] The existing iron resource recovery technology for copper smelting slag still has many deficiencies: for example, some technologies use microwave carbon thermal reduction process, which needs to mix copper smelting slag with reducing agent, binder and other materials to form a ball, and then high-temperature treatment, which has the problems of high equipment cost and limited processing capacity; some direct reduction recovery methods need to modify the copper smelting slag, slow cooling, copper tailing balling and other complex steps, which have the problems of large capital investment and complicated process flow; some technologies use microwave roasting or concentrated sulfuric acid roasting to realize multi-metal recovery, but have the problems of long process flow, large acid consumption, easy production of harmful gases, and need further separation of associated products, which increases the recovery cost and operation difficulty.
[0006] In summary, current comprehensive recovery processes for iron resources in copper smelting slag generally face problems such as complex processes, high costs, and low processing efficiency. There is an urgent need to develop a new technology that is easy to operate, efficient, and economical, in order to achieve the efficient and high-value utilization of iron resources in copper tailings from copper smelting slag. Summary of the Invention
[0007] The purpose of this invention is to provide a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, so as to solve the problems existing in the prior art.
[0008] To achieve the above objectives, the present invention provides the following solution: This invention provides a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, comprising the following steps: The copper smelting slag and copper tailings are leached with sulfuric acid solution, and the leached material is filtered and collected to obtain leaching residue. The leaching residue is ground and then subjected to magnetic separation to obtain iron concentrate product. The concentration of the sulfuric acid solution is 0.1 mol / L to 0.4 mol / L.
[0009] As a further preferred embodiment of the present invention, the leaching temperature is 20°C to 60°C.
[0010] As a further preferred embodiment of the present invention, the leaching time is 10 min to 60 min.
[0011] As a further preferred embodiment of the present invention, the grinding process involves grinding the leaching residue until the proportion of particles that can pass through a 500-mesh standard sieve in the grinding product is not less than 90% (i.e., -500-mesh particles account for more than 90%).
[0012] As a further preferred embodiment of the present invention, magnetic separation is performed in the range of magnetic field strength from 60 kA / m to 200 kA / m.
[0013] As a further preferred embodiment of the present invention, the liquid-to-solid ratio of the leaching is (2-5) mL:1 g.
[0014] In this invention, when treating copper smelting slag tailings with dilute sulfuric acid solution, the core reaction is the chemical reaction between the fir olivine phase (Fe2SiO4) in the tailings and sulfuric acid. This reaction enables the selective decomposition of the fir olivine phase. This process has two key functions: firstly, the decomposed fir olivine enters the leaching solution as a soluble substance, thereby increasing the relative mineral content of magnetite (Fe3O4) in the leaching residue; secondly, it breaks the intergrowth relationship between fir olivine and magnetite, achieving preliminary dissociation between the two and creating favorable conditions for subsequent magnetic separation.
[0015] Regarding the control of process parameters, the concentration of sulfuric acid solution needs to be precisely limited to a specific range (0.1 mol / L to 0.4 mol / L). The purpose is to ensure the full decomposition of the fir olivine phase while avoiding the reaction between magnetite and sulfuric acid (the reaction between magnetite and sulfuric acid requires higher acidity conditions), thereby ensuring the stable retention of magnetite in the leaching residue. The settings of parameters such as leaching temperature, leaching time, and leaching liquid-solid ratio should be set to minimize reagent consumption, energy consumption, and time costs while ensuring the effective decomposition of fir olivine (i.e., achieving a good leaching effect), so as to achieve a balance between process economy and processing efficiency.
[0016] Fe2SiO4(s)+2H2SO4(l)=2FeSO4(l)+H4SiO4(l) Fe3O4(s)+4 H2SO4(l)= FeSO4(l) + Fe2(SO4)3(l) +4 H2O (l) Further fine grinding of the leaching residue obtained after acid leaching can effectively break the intergrowth structure between the residual magnetite and gangue minerals (such as diopside) and the incompletely decomposed fir olivine in the leaching residue, thereby achieving full dissociation of magnetite particles. The dissociated magnetite particles can be more easily adsorbed by magnetic separation equipment in the subsequent magnetic separation process, thus laying the foundation for obtaining iron concentrate with higher iron content.
[0017] In the magnetic separation process, the magnetic field strength needs to be controlled within a specific range (60kA / m~200kA / m): This range ensures that the magnetic magnetite particles are fully adsorbed and recovered, guaranteeing the iron recovery rate; at the same time, it can maximize the separation of non-magnetic gangue minerals (such as diopside) from magnetite, further improving the iron grade of the magnetic concentrate.
[0018] The raw material, copper smelting slag, contains diopside (a non-magnetic silicate mineral with high chemical stability). Under the dilute sulfuric acid leaching conditions specified in this invention (sulfuric acid concentration 0.1mol / L~0.4mol / L, temperature 20℃~60℃), it will hardly react with dilute sulfuric acid, and will not react with the target recovery mineral magnetite, thus avoiding magnetite loss.
[0019] This invention addresses the problem of low iron grade in magnetic concentrate caused by the fine particle size of magnetite and its close association with fir olivine and diopside in copper smelting through a combination of selective acid leaching, fine grinding, and magnetic separation. The acid leaching process preferentially decomposes the fir olivine associated with magnetite, initially breaking the mineral intergrowth structure and creating space for the subsequent separation of diopside and magnetite. The subsequent grinding process (grinding to a particle size of -500 mesh of not less than 90%) further breaks down the intergrowth of diopside and magnetite in the leaching residue, improving their degree of liberation. Finally, the magnetic separation process (magnetic field strength 60kA / m~200kA / m) utilizes the difference between the non-magnetic nature of diopside and the magnetic nature of magnetite to efficiently separate diopside into the magnetic tailings, preventing it from remaining in the magnetic concentrate and diluting the iron grade.
[0020] The present invention discloses the following technical effects: This invention is based on the difference in decomposition properties of fir olivine and magnetite in acidic solutions in copper smelting slag. It achieves selective decomposition of some fir olivine through a dilute sulfuric acid leaching process. This process not only significantly increases the relative mineral content of magnetite in the leaching slag but also breaks the intergrowth structure of magnetite and fir olivine, improving the degree of magnetite liberation. Subsequent grinding and magnetic separation processes further dissociate the encapsulation relationship between magnetite and gangue minerals in the leaching slag, and achieve efficient enrichment of magnetite through magnetic separation. The final iron concentrate obtained has a stable total iron (TFe) grade greater than 59% and an iron recovery rate exceeding 75%, effectively solving the technical problem of efficiently recovering high-grade iron concentrate from copper smelting slag using conventional processes.
[0021] This invention features a simple operating procedure, requiring no complex equipment or harsh conditions such as high temperature and high pressure. It boasts high processing efficiency and controllable costs, effectively reducing the technical requirements and industrial input for iron resource recovery from copper smelting slag. Furthermore, this invention provides a novel technical pathway for the comprehensive recovery of iron resources from copper smelting slag, a secondary resource. It achieves high-value utilization of industrial solid waste while alleviating the pressure on iron resource supply and demand, aligning with the development direction of green metallurgy and resource recycling. It has broad application prospects and promotional value in the field of non-ferrous metal smelting solid waste treatment. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the process flow for improving the iron grade of iron concentrate from copper smelting slag and tailings magnetic separation according to the present invention. Detailed Implementation
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0026] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0027] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0028] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0029] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0030] The copper smelting slag used in the following embodiments and comparative examples of the present invention was provided by a copper smelting enterprise. Its main elemental composition is shown in Table 1, and the main phases of iron are shown in Table 2.
[0031] Table 1. Main elemental composition of copper smelting slag from a copper smelter (%) Table 2. Main phases (%) of copper smelting slag from a copper smelter A schematic diagram of the process flow for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings in this invention is shown below. Figure 1 .
[0032] The present invention will be further described in detail below with reference to embodiments: Example 1 This embodiment provides a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, the steps of which are as follows: 100g of copper smelting slag (selected copper tailings) was weighed and added to a reaction vessel containing 500mL of 0.1mol / L sulfuric acid solution. The mixture was stirred and leached at a constant temperature of 60℃ for 60min. After leaching, the reaction system was filtered, and the leaching residue was collected. The weight of the leaching residue was 94.5g. Analysis showed that the total iron (TFe) content in the leaching residue was 51.28%, of which magnetite mineral content was 73.0%.
[0033] Subsequently, 10g was accurately weighed from the leaching residue as a sample to be processed, and ground using a three-roll four-cylinder mill until the proportion of particles with a size of -500 mesh in the grinding product was not less than 90%. The ground material was then placed in a magnetic separator with a magnetic field strength of 150kA / m for magnetic separation, ultimately yielding 7.57g of magnetic concentrate. Chemical elemental analysis of the magnetic concentrate revealed that the total iron (TFe) content was 59.12%; based on the initial copper smelting slag tailings, the iron recovery rate in this embodiment was 84.41%.
[0034] Example 2 This embodiment provides a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, the steps of which are as follows: 100g of copper smelting slag (copper tailings) was weighed and added to a reaction vessel containing 300mL of 0.2mol / L sulfuric acid solution. The mixture was continuously stirred and leached at a constant temperature of 40℃ for 30min. After leaching, the reaction mixture was filtered, and the leaching residue was collected. The weight of the leaching residue was 90.8g. Analysis showed that the total iron (TFe) content in the leaching residue was 52.54%, of which magnetite mineral content was 76.0%.
[0035] Next, 10g was accurately weighed from the leaching residue as a sample for subsequent processing and ground using a three-roll four-cylinder mill until the proportion of particles with a size of -500 mesh in the grinding product reached 92%. The ground material was then fed into a magnetic separator with a magnetic field strength of 120kA / m for magnetic separation, ultimately obtaining 7.57g of magnetic concentrate. Chemical elemental analysis of the magnetic concentrate revealed that the total iron (TFe) content was 59.25%; based on the initial copper smelting slag tailings, the iron recovery rate in this embodiment was 81.29%.
[0036] Example 3 This embodiment provides a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, the steps of which are as follows: 100g of copper smelting slag (selected copper tailings) was weighed and added to a reaction vessel containing 500mL of 0.3mol / L sulfuric acid solution. The mixture was stirred and leached at a constant temperature of 20℃ for 20min. After leaching, the reaction system was filtered, and the leaching residue was collected. The weight of the leaching residue was 86.7g. Analysis showed that the total iron (TFe) content in the leaching residue was 51.77%, of which magnetite mineral content was 73.0%.
[0037] Subsequently, 10g was accurately weighed from the leaching residue as a sample to be processed, and ground using a three-roll four-cylinder mill until the proportion of particles with a size of -500 mesh in the grinding product was not less than 92%. The ground material was then placed in a magnetic separator with a magnetic field strength of 60kA / m for magnetic separation, ultimately yielding 7.42g of magnetic concentrate. Chemical elemental analysis of the magnetic concentrate revealed that the total iron (TFe) content was 59.12%; based on the initial copper smelting slag tailings, the iron recovery rate in this embodiment was 75.91%.
[0038] Example 4 This embodiment provides a method for improving the iron grade of magnetic separation iron concentrate from copper smelting slag tailings, the steps of which are as follows: 100g of copper smelting slag (selected copper tailings) was weighed and added to a reaction vessel containing 200mL of 0.4mol / L sulfuric acid solution. The mixture was stirred and leached at a constant temperature of 30℃ for 60min. After leaching, the reaction system was filtered, and the leaching residue was collected. The weight of the leaching residue was 85.2g. Analysis showed that the total iron (TFe) content in the leaching residue was 52.18%, of which magnetite mineral content was 73.0%.
[0039] Subsequently, 10g was accurately weighed from the leaching residue as a sample to be processed, and ground using a three-roll four-cylinder mill until the proportion of particles with a size of -500 mesh in the grinding product was not less than 90%. The ground material was then placed in a magnetic separator with a magnetic field strength of 150kA / m for magnetic separation, ultimately yielding 7.87g of magnetic concentrate. Chemical elemental analysis of the magnetic concentrate revealed that the total iron (TFe) content was 59.03%; based on the initial copper smelting slag tailings, the iron recovery rate in this embodiment was 79.0%.
[0040] Comparative Example 1 The only difference from Example 1 is that the copper smelting slag tailings were not pretreated with acid leaching. The specific steps are as follows: 10g of copper smelting slag tailings was weighed and ground using a three-roller four-cylinder mill until the proportion of particles with a size of -500 mesh in the grinding product was not less than 90%. The ground material was then placed in a magnetic separator with a magnetic field strength of 150kA / m for magnetic separation, and finally 7.31g of magnetic concentrate was obtained.
[0041] The total iron (TFe) content in the magnetic concentrate was found to be 56.04%; based on the initial copper smelting slag tailings, the iron recovery rate in this comparative example was 72.77%.
[0042] Comparative Example 2 The only difference from Example 1 is that the copper smelting slag tailings, after acid leaching, were not subjected to grinding treatment but directly underwent magnetic separation. The specific steps are as follows: 10g of copper smelting slag and copper tailings were weighed and added to 50mL of 0.1mol / L sulfuric acid solution. The mixture was stirred and leached at a constant temperature of 60℃ for 60min to complete the acid leaching treatment. After leaching, the leaching residue was collected by filtration. No grinding was required. The leaching residue was directly placed in a magnetic separator with a magnetic field strength of 150kA / m for magnetic separation. Finally, 7.86g of magnetic concentrate was obtained.
[0043] The total iron (TFe) content in the magnetic concentrate was found to be 54.15%; based on the initial copper smelting slag tailings, the iron recovery rate in this comparative example was 67.31%.
[0044] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method of improving the iron grade of a magnetic separated iron concentrate from copper tailings of copper smelting slag, characterized in that, The method comprises the following steps: The copper tailings of copper smelting slag are leached by a sulfuric acid solution, filtered, and the leaching residue is collected; The leaching residue is ground and treated, and then subjected to magnetic separation to obtain an iron concentrate product; The concentration of the sulfuric acid solution is 0.1-0.4 mol / L.
2. The process of improving the iron grade of the magnetic separated iron concentrate from copper smelting slag copper tailings according to claim 1, characterized in that, The leaching temperature is 20-60 DEG C.
3. The process as claimed in claim 2, wherein the process is characterized by, The leaching time is 10-60 min.
4. The process as claimed in claim 1, wherein the process for improving the iron grade of the magnetic separated iron concentrate of the copper recovery tailings of copper smelting slag is characterized by, The grinding treatment is to grind the leaching residue to a particle size such that the particles passing through a 500-mesh standard sieve account for not less than 90% of the grinding product.
5. The process as claimed in claim 1, wherein the process for improving the iron grade of the magnetic separated iron concentrate of the copper recovery tailing of the copper smelting slag is characterized by, The magnetic separation is performed at a magnetic field strength of 60-200 kA / m.
6. The process as claimed in claim 1, wherein the process for improving the iron grade of the magnetic separated iron concentrate of the copper recovery tailing of the copper smelting slag is characterized by, The liquid-solid ratio of the leaching is (2-5) mL:1 g.